William and the lost spirit - Bonneval, Gwen de; Bonhomme, Matthieu; Smith, Anne Collins; Smith, Owen, (Owen M.) (Minneapolis : Graphic Universe, 2013)
"In this graphic novel that combines medieval legends and folklore, the brutish feudal world, and devotion to family, William, the grandson of an elderly feudal lord in the thirteenth century, sets out on a labyrinthine journey to discover his father's killer"--Provided by publisher.
Keywords: Middle Ages -- Fiction; Knights and knighthood -- Fiction; Voyages and travels -- Fiction; Families -- Fiction; Mythology -- Fiction; Graphic novels; Folklore